2013
DOI: 10.1542/peds.2013-0152
|View full text |Cite
|
Sign up to set email alerts
|

Parental Preferences and Goals Regarding ADHD Treatment

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Shared decision-making involves the assessment of preferences and goals and has been prioritized in new attention-deficit/hyperactivity disorder treatment guidelines, yet no studies have examined the impact of both preferences and goals on treatment initiation. WHAT THIS STUDY ADDS:Supporting the clinical utility of preference and goal assessment, we found that parental treatment preferences are associated with treatment initiation, and those with distinct goals select different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 36 publications
1
44
0
2
Order By: Relevance
“…ADHD medications are now the most commonly prescribed medication class in adolescents [57] with academic functioning being the primary treatment target in many cases. Parents preferentially lean toward medication options when trying to address academic concerns [58] despite no clear evidence that they are more effective than behavioral interventions. Recent shifts in government policies regarding public education may be driving this trend in the US.…”
Section: Trends In Medication Prescription Ratesmentioning
confidence: 99%
“…ADHD medications are now the most commonly prescribed medication class in adolescents [57] with academic functioning being the primary treatment target in many cases. Parents preferentially lean toward medication options when trying to address academic concerns [58] despite no clear evidence that they are more effective than behavioral interventions. Recent shifts in government policies regarding public education may be driving this trend in the US.…”
Section: Trends In Medication Prescription Ratesmentioning
confidence: 99%
“…(3–5) However, prior research has not elicited caregivers’ priorities that may influence decisions to initiate medication for their child. (7, 9) Therefore, this feasibility study aimed to develop and pilot a best-worst scaling instrument that would assess caregivers’ priorities when initiating ADHD medicine for their child. The _________ Institutional Review Board (IRB) approved the study and granted a waiver of informed consent.…”
Section: Introductionmentioning
confidence: 99%
“…Adjunctive behavioral parent training is useful for mothers who have parental self-efficacy and for children with or without single-type (16). Strong evidence proves that parent training and cognitive behavioral therapy have useful effect on ADHD symptoms (21)(22)(23)(24). Frolich in a study assessed 18 children with ADHD and used six sessions of cognitive behavioral therapy as well as six sessions of parent training; results showed that ADHD symptoms were reduced at home and school (25).…”
Section: Discussionmentioning
confidence: 99%